The synergistic interaction effect between biochar and plant growth-promoting rhizobacteria on beneficial microbial communities in soil - Zou, Qianmei; Zhao, Longyuan; Guan, Lirong; Chen, Ping; Zhao, Jie; Zhao, Yueying; Du, Yunlong; Xie, Yong (Frontiers in Plant Science, 2024)
Excessive use of chemical fertilizers and extensive farming can degrade soil properties so that leading to decline in crop yields. Combining plant growth-promoting rhizobacteria (PGPR) with biochar (BC) may be an alternative way to mitigate this situation. However, the proportion of PGPR and BC at which crop yield can be improved, as well as the improvement effect extent on different eco-geographic region and crops, remain unclear. This research used cabbage [Brassica pekinensis (Lour.) Rupr.] as the target crop and established as treatment conventional fertilization as a control and a 50% reduction in nitrogen fertilizer at the Yunnan-Guizhou Plateau of China, adding BC or PGPR to evaluate the effects of different treatments on cabbage yield and the soil physicochemical properties. Specifically, high-throughput sequencing probed beneficial soil microbial communities and investigated the impact of BC and PGPR on cabbage yield and soil properties. The results revealed that the soil alkaline hydrolyzable nitrogen (AH-N), available phosphorus (AP), and available potassium (AK) contents were higher in the BC application than in control. The BC application or mixed with PGPR significantly increased the soil organic matter (OM) content (P<0.05), with a maximum of 42.59 g/kg. Further, applying BC or PGPR significantly increased the abundance of beneficial soil microorganisms in the whole growth period of cabbage (P<0.05), such as Streptomyces, Lysobacter, and Bacillus. Meanwhile, the co-application of BC and PGPR increased the abundance of Pseudomonas, and also significantly enhanced the Shannon index and Simpson index of bacterial community (P<0.05). Combined or not with PGPR, the BC application significantly enhanced cabbage yield (P<0.05), with the highest yield reached 1.41 fold of the control. Our research indicated that BC is an suitable and promising carrier of PGPR for soil improvement, combining BC and PGPR can effectively ameliorate the diversity of bacterial community even in acid red soil rhizosphere, and the most direct reflection is to improve soil fertility and cabbage yield.